Investigating the influence of attractiveness and value for money on revisit intention for Toraja-Londa’s cultural sustainability - Darmawan, Armin; Hellavani, Hellavani; Setiawan, Irwan; Handayani, Dwi; Gunawan, Imam (Universitas Pendidikan Indonesia, 2026)
AbstractThis study examines the factors influencing revisit intention to cultural heritage sites, specifically focusing on the roles of perceived attractiveness and perceived value for money, with customer satisfaction serving as a mediating factor. The proposed conceptual model is empirically tested using data collected from 130 tourists who visited Toraja-Londa, a prominent cultural heritage destination. Employing Partial Least Squares Structural Equation Modeling (PLS-SEM), the analysis reveals a strong correlation between the antecedents of customer behavioral practices and revisit intention. The findings indicate that both perceived attractiveness and perceived value for money significantly enhance customer satisfaction, which in turn plays a crucial moderating role in shaping revisit intention. This research provides valuable insights for both theoretical and managerial perspectives, highlighting the importance of fostering a positive relationship between perceived attractiveness, value for money, satisfaction, and revisit intention. The study's findings offer practical implications for policymakers and stakeholders, enabling them to make informed decisions that enhance the sustainability and appeal of cultural heritage tourism destinations. By understanding the drivers of revisit intention, destination managers can develop targeted strategies to improve visitor experiences and encourage repeat visits. AbstrakStudi ini mengkaji faktor-faktor yang memengaruhi niat kunjungan ulang ke situs warisan budaya, khususnya berfokus pada peran persepsi daya tarik dan persepsi nilai uang, dengan kepuasan pelanggan sebagai faktor mediasi. Model konseptual yang diusulkan diuji secara empiris menggunakan data yang dikumpulkan dari 130 wisatawan yang mengunjungi Toraja-Londa, sebuah destinasi warisan budaya terkemuka. Dengan menggunakan Pemodelan Persamaan Struktural Kuadrat Terkecil Parsial (PLS-SEM), analisis ini mengungkapkan korelasi yang kuat antara anteseden praktik perilaku pelanggan dan niat kunjungan ulang. Temuan menunjukkan bahwa persepsi daya tarik dan persepsi nilai uang secara signifikan meningkatkan kepuasan pelanggan, yang pada gilirannya memainkan peran moderasi krusial dalam membentuk niat kunjungan ulang. Penelitian ini memberikan wawasan berharga bagi perspektif teoretis dan manajerial, menyoroti pentingnya membina hubungan positif antara persepsi daya tarik, nilai uang, kepuasan, dan niat kunjungan ulang. Temuan studi ini menawarkan implikasi praktis bagi para pembuat kebijakan dan pemangku kepentingan, memungkinkan mereka untuk membuat keputusan yang tepat yang meningkatkan keberlanjutan dan daya tarik destinasi wisata warisan budaya. Dengan memahami faktor pendorong minat berkunjung kembali, pengelola destinasi dapat mengembangkan strategi yang tepat guna meningkatkan pengalaman pengunjung dan mendorong kunjungan berulang.